May I calculate your taxes? The effect of bookkeeping on tax compliance under a simplified regime - Rosangela Bando Grana; Otavio Canozzi; José Martínez; Ana Lucía Dezolt (Inter-American Development Bank (IDB), 2021)
Many countries worldwide face significant miss reporting in tax declarations. Miss reporting leads to undesired low revenue and economic distortions. This paper discusses the extent to which the residual bookkeeping burden faced by small firms in simplified regimes influence tax declarations. A randomized control trial among 1,500 irregular firms in Piaui, Brazil showed that adding the tax amount due and records on transactions to a warning notification improved compliance in 21 percentage points and increased the reported revenue in 39 percent. Firms without an accountant were less likely to regularize their status without the added information. These findings suggest the use of third party information to support voluntary compliance may present an opportunity for digital services to improve tax revenue services.
Keywords: H26; H30; H32; O38; 330; Tax payer support; tax compliance; accounting